POLYMERIC COMPOSITE ELASTIC CONSTANTS DETERMINATION ON THE BASIS OF MODIFIED TECHNIQUE. THEORETICAL & NUMERICAL ANALYSIS - А.A. BYCHKOV; A.N. SOLOVIEV; A.V. FOMIN; O.D. PAHANYAN; S.N. SHEVTSOV (Advanced Engineering Research)
The V-notch (standard ASTM D5379-93) shear test was investigated for determining the in-plane shear modulus. With purpose of lateral response exception the new scheme of test with specimen symmetrical loading is offered. For standard and modified schemes the comparative finite element analysis of state in a specimen's working area is executed. This analysis allow to determine the shape and sizes of a pure shear zone at different orientations of reinforcing fibers and geometrical tolerances, and to estimate error in determination of a shear modulus stipulated by averaging of shear stresses in specimen's working section. The results have shown full coincidence of stress-strained states at standard and modified schemes of tests. Our numerical evaluation shows that even for specimens with ideal shape using of mean shearing stress (relation of an applied force to a sectional area between notches) always increase error of shear module determination more than 15 % and for obtaining more precise results it is necessary to padding definition of shear stresses in center of a working area with FEM analysis. For using in actual experiment, when there are geometrical errors of the shape and fastening of specimens, but the remaining modules are determined irrespective of considered tests, the effective iterative scheme on the FEM based numerical experiment for refinement and for definition of a shear modulus values confidence interval is offered.